Low Vitamin D Levels Are Associated with Both Iron Deficiency and Anemia in Children and Adolescents. (1st March 2015) - Lee, Jun Ah; Hwang, Jin Soon; Hwang, Il Tae; Kim, Dong Ho; Seo, Ju-Hee; Lim, Jung Sub
Abstract : Background : We aimed to examine the association between vitamin D deficiency and anemia in a nationally representative sample of Korean children and adolescents. Methods : Cross-sectional data on 2526 children and adolescents aged 10–20 years from the Korea National Health and Nutrition Examination Survey-V (2010–2012) were used. Anemia was defined according to specifications of the World Health Organization. Iron deficiency was defined as serum ferritin level of <12 ng/mL and transferrin saturation (TSAT) <16%. Results : The prevalence of vitamin D deficiency in Korean children and adolescents was high especially in female (35.7% vs. 50.9%, P < 0.001). The prevalence of anemia was also higher in female (1.1% vs. 6.8%; P < 0.001). In logistic regression, risk factors for anemia were female sex, old age, post-menarche, low household income, vitamin D deficiency, and iron deficiency. The Odds Ratio for anemia, iron deficiency and iron deficiency anemia (IDA) in subjects with vitamin D deficiency (<15 ng/mL) were 1.81(95% CI, 1.13–2.88), 1.94(95% CI, 1.27–2.97), and 2.26 (95% CI, 1.20–4.24) after controlling for other risk factors. However, after examining the sexes separately, only female subjects showed statistical significance. After further controlling for iron deficiency, the risk of anemia was not significant ( P = 0.261). Conclusions : Vitamin D deficiency is associated with increased risk of anemia, especially iron deficiency anemia, in healthy female children and adolescents. However, the association is attenuated after adjustment for iron deficiency. Further studies are needed to determine whether vitamin D deficiency is the cause of anemia, or bystander of nutritional deficiency which cause iron deficiency.